2011
DOI: 10.1097/igc.0b013e318222cfdd
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Iron-Induced Oxidative Stress in the Pathogenesis of Clear Cell Carcinoma of the Ovary

Abstract: These aspects of reactive oxygen species biology will be discussed in the context of its relationship to EAOC carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 34 publications
(56 reference statements)
2
40
0
Order By: Relevance
“…In general, hemochromatosis, chronic viral hepatitis, inflammatory bowel diseases such as Crohn's disease and ulcerative colitis or asbestosis induce iron overload, which may lead to hepatocellular carcinoma, colon cancer or mesothelioma in humans (69). Several investigators have demonstrated that iron-induced oxidative stress is also able to induce specific gene modifications in endometriosis-associated ovarian cancer (27,28,(71)(72)(73)(74). Undefined molecular events occurring in endo metriosis that has undergone Müllerian metaplasia may initiate neoplastic change towards not only carcinoma, but also sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…In general, hemochromatosis, chronic viral hepatitis, inflammatory bowel diseases such as Crohn's disease and ulcerative colitis or asbestosis induce iron overload, which may lead to hepatocellular carcinoma, colon cancer or mesothelioma in humans (69). Several investigators have demonstrated that iron-induced oxidative stress is also able to induce specific gene modifications in endometriosis-associated ovarian cancer (27,28,(71)(72)(73)(74). Undefined molecular events occurring in endo metriosis that has undergone Müllerian metaplasia may initiate neoplastic change towards not only carcinoma, but also sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of this study successfully identifies a set of candidate susceptibility genes for HNF-1β. The preliminary data showed that Chk1 protein is persistently activated in the HNF-1β-overexpressing CCC cells (64). Clinically, relevant drugs targeting proteins connected in the HNF-1β network may be the Chk1 inhibitors.…”
Section: Targeting Src Dasatinib and Saracatinib (Azd0530)mentioning
confidence: 99%
“…Chk1 might function in the cellular survival pathways that enhance DNA damage repair, thereby granting chemoresistance. Chk1 inhibition selectively chemosensitizes HNF-1β-overexpressing CCC cells in vitro (64). The Chk1 inhibitor might be a novel target for developing cancer therapeutics in the HNF-1β-positive cells that can potentially enhance the sensitivity to chemotherapeutic agents acting via induction of DNA damage and apoptosis.…”
Section: Targeting Src Dasatinib and Saracatinib (Azd0530)mentioning
confidence: 99%
“…Clear cell carcinoma and endometrioid adenocarcinoma exhibit distinct clinicopathological features and molecular phenotypes (19,20). Yamada et al (21) hypothesized that heme and iron-induced signals contribute to carcinogenesis via three major mechanisms: i) By enhancing oxidative stress, which promotes DNA mutagenesis and contributes to tumor initiation; ii) via activation of detoxification pathways, thereby contributing to tumor promotion; iii) by sustaining growth of cancer cells via estrogen-dependent (endometrioid) or -independent (clear cell) mechanisms. These studies provide novel insights into the pathophysiology and significance of genetic functional categories in EAOC.…”
Section: Molecular Changes Implicated In Clear Cell Carcinomamentioning
confidence: 99%